A BRIEF LOOK AT AND COMMENTS ON THE SOCIAL LIFE IN â€œTHE ADVENTURE OF TOM SAWYERâ€ BY MARK TWAIN - Rachayu, Imma (JURNAL LITERARY CRITICISM, 2015)
Prose is one of the three literary kinds. Sub kinds of prose are history, description, biography, fiction, reflection, persuasion, censure and humor. The writer will take one sub-genre of prose only, which is fiction. Fiction is action, which primarily appeals to the imagination. This research aims to find the properties of the novel and the social life and comments described in the novel. The scope of the study is limited only a brief look and comments on the social life in ?Adventure of Tom Sawyer by Mark Twain?. Data analysis was conducted with the qualitative analysis. The results showed that there was seven elements, which are the biography of the author, the list of his writings, the summary of the adventure of Tom Sawyer, the theme, the plot, the characters, the setting and points of view. In answered the second questions about two aspects consist of; a) human beings has good behaviour, he will do positive activities in the social life such as human beings are not descrimination of racial in their environment. They have a good nature, the nature of love, patience, wisdom, kindness, simplicity, the nature of protection and responsibility and than have the potency to belief in God, b) human beings has bad behaviour, he will not do the positive or good activities in the social life, because there were some the economic gaps in their environment which make them have identical the nature of greed, selfish, arrogance, stinginess and ambitions in their life. Meanwhile, the social life in our environment can make us become mature and care with other people. We have to be able give good services to each other and try to avoid bad behavior which may depress ourselves. Keywords : a brief look at, comments, social life, the adventure of Tom Sawyer, Mark Twain